Pengaruh Penggunaan Media Pembelajaran Audio Visual Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Matematika Kelas V Sdn 023 Pandau Jaya - Shelvi, Shelvi cahyani; Ain, Siti Quratul (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Student learning motivation at V SDN 023 Pandau Jaya, Kampar Regency is still relatively low. The aim of thisresearch is to determine the effect of using audio-visual learning media on students' learning motivation in ClassV mathematics subjects at SDN 023 Pandau Jaya, Kampar Regency. The research method is quantitative with apopulation of fifth grade students with a sampling technique using purposive sampling. So the sample is 30students. Data was collected through a questionnaire and processed using hypothesis testing with the help ofSPSS Version 22. Based on the results of the analysis through hypothesis testing, namely the paired sample t testwith a sig (2-tailed) value of 0.000 < 0.05, it is stated that the working hypothesis (Ha) in this study is acceptedand the hypothesis (Ho) is declared rejected. The increase in the posttest questionnaire was 15,100 due to the useof audio-visual learning media